Mengoptimalkan Penggunaan Youtube Sebagai Media Pembelajaran Untuk Meningkatkan Prestasi Belajar Siswa SMK - Warju, Warju -; Ariyanto, Sudirman Rizki; Umaroh, Susi Tri; Pratama, Muhammad Yandi; Nugraha, Ata Syifa (Universitas Negeri Yogyakarta, 2024)
This research aims to analyze the effectiveness of learning media and mathematical logic intelligence on student learning achievement. This research was a quasi-experimental type with a sample size of 68 students consisting of an experimental class and a control class of 34 students each. The data analysis method uses two-way Anova. The results of this study indicate that there are (1) differences in learning achievement between students who study using YouTube compared to e-books; (2) differences in learning achievement between students with high versus low mathematical logical intelligence; and (3) the interaction between learning media and mathematical logic intelligence on student learning achievement.